https://insanvetoplum.org/en/issues/9-4/M0327 - Engin Arık; Beril Tezeller Arık (İnsan & Toplum)
What do the terms “psychology” and “psychologist” mean? Using the prototype theory and corpus semantics, this study aims to reveal the meanings of these words in everyday language. The data were collected from Twitter between September 2017 and January 2019. A total of 25,492 tweets contained the term “psychology.” These tweets consisted of 451,346 words. A total of 15,651 tweets contained the term “psychologist.” These tweets consisted of 279,762 words. The results showed that the term “psychology” was related to the following categories, ordered according to their frequency: QUALITY, QUANTITY, OCCUPATION, EDUCATION, MIND, PERSON, and BELIEF. Meanwhile, the term “psychologist” was related to QUALITY, QUANTITY, EDUCATION, PERSON, OCCUPATION, and JOB-TITLE. Moreover, both the terms “psychology” and “psychologist” had the coordination construction (X and Y: psychology and philosophy, psychologist and psychiatrist). The term “psychologist” also had the description construction (X is Y: a psychologist friend) and the likening construction (X as Y: speaking like a psychologist). Furthermore, these words were used significantly more frequently in n-grams such as psychology no more [meaning demoralized] and I want to be a psychologist. As a result, the meanings of these words do not completely overlap those in the dictionaries and in the profession. Therefore, the dictionary entries and the professional definitions should be improved and academics and professionals should use social media more actively